Evaluation of Full-Scale Concrete Frames Exposed to Natural Fires at Early Ages. - Muhammad Ismaiel Omer; Dilshad Kakasoor Jaf (Zanco Journal of Pure and Applied Sciences, 2020)
This article presents the evaluation of full scale reinforced concrete frames subjected to natural fire at early age. The test program consisted of constructing three large frames of reinforced concrete as well as revealing them to the natural fire by shooting their formwork when the age of concrete achieves three and five days. The evaluation of reinforced concrete frames was done by the load test method as described in the American Concrete Institute (ACI), namely the 24 hrs load test method, which is evaluation criteria that have been in use for several decades. For each frame, the structural evaluation based on deflection criteria is discussed. Results showed that the frame exposed early to natural fire was generally more affected than the other frame, as its midspan deflection was increased to about 109% if compared to frame not exposed to fire.